The Important Role of Traditional Games in Enchancing Children’s Gross Motor: Literature Review - Afifah Maulidiyyah, Aisyah Nur; Purwoko, Budi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
Gross motor development involves body movements that engage large muscles, such as sitting, walking, and running. Participation in motor activities is crucial for a child's development. Through active physical activities, children can enhance their gross motor skills. One approach to developing these skills is through traditional games. However, with the advancement of science and technology, children tend to be more interested in and easily access gadget games rather than traditional games. This shift has led to a lack of social interaction among children and limitations in the development of gross motor skills. Recognizing this phenomenon, researchers conducted a literature review to identify the important role of traditional games in improving children's gross motor skills. This study employed a literature review or literature survey method, utilizing supplementary data from previous research with a similar topic. Data collection was conducted using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. The findings of the literature review concluded that traditional games can provide a solution for enhancing the development of children's gross motor skills.